1984
DOI: 10.1111/j.1525-1446.1984.tb00437.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Education on Self‐Care Agency

Abstract: This study examined the effects of group education classes on self-care agency (SCA) of individuals with chronic obstructive pulmonary disease (COPD) and assessed the four independent variables of presence of a significant other, severity of disease, social status, and type of lung disease, and the persons' relationships to SCA and to the change in SCA after education. A Address correspondence to: Rebecca Stockdale-Wdb, m, MSN, 2 ~~d bee, Ament #I, New Haven, CT 06511. Telephone (203) 785-9286. 97

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1992
1992
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…The findings indicated that those who participated in the educational program had fewer hospital admissions, shorter lengths of stay in hospitals, and longer lengths of stay in the community. Stockdale-Woolley (1984) tested the effects of education on the self-care agency of 25 patients with COPD. Self-care agency scores were si@cantly greater after the classes than they were before.…”
Section: Health Belief Modelmentioning
confidence: 99%
“…The findings indicated that those who participated in the educational program had fewer hospital admissions, shorter lengths of stay in hospitals, and longer lengths of stay in the community. Stockdale-Woolley (1984) tested the effects of education on the self-care agency of 25 patients with COPD. Self-care agency scores were si@cantly greater after the classes than they were before.…”
Section: Health Belief Modelmentioning
confidence: 99%
“…The authors concluded that they had a valid and reliable instrument to measure exercise of self-care agency. The instrument was used previously in a clinical study of patients with chronic obstructive pulmonary disease, where reliability was 0.92 for internal consistency [16]. McBride [24] tested construct validity and re-liability of the instrument with 62 nursing students and 57 adult diabetic patients.…”
Section: Instrumentsmentioning
confidence: 99%
“…Number 3· MaylJun 1993 ney and Fleischer (1979) originally established the construct validity of the instrumentby comparing ESCA to items of the Adjective Check List (Gough & Heilbrun, 1965). The internal consistencyof the ESCA instrument was evaluatedby administering the scale to nursing and psychology students and the reliability coefficient ranged from .77 to .80 (Kearney & Fleischer, 1979).Test-retest reliability of the instrument was .77 for 76 nursing students (Kearney & Fleischer, 1979)and reliability ranged from .79 to .94 in a sample of chronically ill individuals (Stockdale-Woolley, 1984). Riesch and Hauck (1988) further validated the four factors of ESCAwiththree distinctsamples: pregnantwomenand their labor coaches (n = 100); healthy adolescents (n =110); and universityfaculty, staff, and students (n =296).…”
Section: Study Instnunentmentioning
confidence: 99%
“…Researchers have begun to identify interventions that enhance the self-care ability ofchronically ill individuals (Beckie, 1989;Goeppinger, Arthur, Baglioni, Brunk, & Brunner, 1989;Huss, Salerno, & Huss, 1991;Maes & Schlosser, 1988;Perry, 1981;Rubin, Peyrot, & Saudek, 1989;Stockdale-Woolley, 1984;Winkler, Underwood, Fatovich, James, & Gray, 1989). In these studies, education formed the major component of the intervention, and the education-except in the study conducted by Beckie (1989)-was not individualized to each participant's personal situation.…”
mentioning
confidence: 99%